Thermally conductive sheet and method of producing thermally conductive sheet
The thermal conductivity sheet addresses the issue of high contact resistance in thin sheets by incorporating a second layer with specific smoothness criteria, ensuring effective heat dissipation and reduced thermal resistance in electronic devices.
Patent Information
- Application Number
- JP2023114509
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-24
AI Technical Summary
Conventional thermal conductivity sheets with carbon fibers arranged in the thickness direction face challenges in reducing contact thermal resistance, especially when thin, due to surface roughness and increased resistance, which hinders efficient heat dissipation in electronic devices.
A thermal conductivity sheet is designed with a first layer containing a binder resin, anisotropic thermal conductive material, and inorganic filler, and a second layer on both sides with a binder resin and inorganic filler, ensuring a smooth surface with a deployment area ratio of 35% or less and skewness of -1.0 or less, enhancing surface smoothness and reducing contact thermal resistance.
The sheet achieves reduced thermal resistance values even at thin film thicknesses, improving heat dissipation efficiency in electronic devices by maintaining good adhesion and surface smoothness, thus enhancing thermal conductivity.
Smart Images

Figure 2025012003000001_ABST
Abstract
Description
[Technical field]
[0001] The present technology relates to a thermally conductive sheet and a method for manufacturing the thermally conductive sheet. [Background technology]
[0002] With the further improvement of the performance of electronic devices, the density and mounting of semiconductor elements are increasing. In proportion to this, the amount of heat generated and the heat density from ICs and the like also tend to increase, and it is required to transfer heat to heat sinks such as heat dissipation fans and heat sinks more efficiently through thermally conductive sheets. In addition, electronic devices are rapidly becoming smaller and thinner, and the thickness of the required thermally conductive sheets also tends to become thinner, and there is a demand for sheets with lower thermal resistance. One example of a material that meets this demand is a thermally conductive sheet using carbon fibers (see, for example, Patent Documents 1, 3, and 7). Carbon fibers are an anisotropic filler with a thermal conductivity of about 600 to 1200 W / (m·K) in the fiber direction, and it is known that the thermal conductivity is dramatically improved by orienting the carbon fibers in the thickness direction of the thermally conductive sheet, which is the heat transfer direction.
[0003] In a thermally conductive sheet in which carbon fibers are oriented in the thickness direction of the thermally conductive sheet, the carbon fibers tend to protrude from the sheet surface, resulting in a rough surface and a high contact thermal resistance between the thermally conductive sheet and the adherend. In addition, if the thickness of the thermally conductive sheet is thin, the effect of such contact thermal resistance tends to be large, and even if a material with high thermal conductivity in bulk is used, it may be difficult to reduce the thermal resistance of the entire thermally conductive sheet, especially in a low load region.
[0004] Methods for reducing the contact thermal resistance of a thermally conductive sheet include making the surface of the thermally conductive sheet smoother by using a manufacturing method that includes a step of pressing the thermally conductive sheet or a step of polishing the surface of the thermally conductive sheet (see, for example, Patent Documents 6 and 7).
[0005] Thus, improving the smoothness of a thin thermally conductive sheet and reducing the contact thermal resistance is one of the major challenges. Therefore, a method is desired that can provide a thermally conductive sheet with reduced contact thermal resistance even if the sheet is thin, with fewer steps, for example, without using a step of pressing the thermally conductive sheet or a step of polishing the surface of the thermally conductive sheet. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5752299 [Patent Document 2] Patent No. 4716102 [Patent Document 3] JP 2020-116873 A [Patent Document 4] Patent No. 6105388 [Patent Document 5] Patent No. 6846641 [Patent Document 6] Patent No. 6631735 [Patent Document 7] Patent No. 6650175 Summary of the Invention [Problem to be solved by the invention]
[0007] The present technology has been proposed in consideration of the conventional situation, and provides a thermally conductive sheet in which the contact thermal resistance is reduced even when the film thickness is thin, and thus the thermal resistance value of the entire thermally conductive sheet during actual use is reduced. [Means for solving the problem]
[0008] The thermally conductive sheet according to the present technology comprises a first thermally conductive layer containing a first binder resin, an anisotropic thermally conductive material, and a first inorganic filler, and a second thermally conductive layer provided on both sides of the first thermally conductive layer, containing a second binder resin and a second inorganic filler, having a thickness of more than 4 μm and less than 20 μm, and having a thermal conductivity of 0.8 W / (m·K) or more, wherein the developed area ratio of at least one of the surfaces of the second thermally conductive layer is 35% or less and the skewness of at least one of the surfaces of the second thermally conductive layer is -1.0 or less, as measured using a scanning white light interference microscope with an objective lens of 20x, as specified in ISO 25178.
[0009] A manufacturing method for a thermally conductive sheet according to the present technology includes the steps of: forming a first thermally conductive layer containing a first binder resin, an anisotropic thermally conductive material, and a first inorganic filler; and forming, on both sides of the first thermally conductive layer, a second thermally conductive layer containing a second binder resin and a second inorganic filler, having a thickness of more than 4 μm and less than 20 μm, and having a thermal conductivity of 0.8 W / (m·K) or more, wherein the developed area ratio of at least one of the surfaces of the second thermally conductive layer is 35% or less and the skewness of at least one of the surfaces of the second thermally conductive layer is -1.0 or less, as measured using a scanning white light interference microscope with an objective lens of 20x, as specified in ISO 25178. Effect of the Invention
[0010] The present technology can provide a thermally conductive sheet in which the contact thermal resistance is reduced even when the film thickness is thin, and thus the thermal resistance value of the entire thermally conductive sheet during actual use is reduced. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a thermally conductive sheet according to the present technology. [Diagram 2] FIG. 2 is a photograph of the surface of a thermally conductive sheet when the second thermally conductive layer has a surface skewness of −1.7, as measured with a scanning white light interference microscope. [Diagram 3]FIG. 3 is a height histogram of the thermally conductive sheet when the skewness of the surface of the second thermally conductive layer is −1.7. [Figure 4] FIG. 4 is a photograph of the surface of a thermally conductive sheet when the second thermally conductive layer has a surface skewness of −0.63, as measured with a scanning white light interference microscope. [Diagram 5] FIG. 5 is a height histogram of the thermally conductive sheet when the skewness of the surface of the second thermally conductive layer is −0.63. [Figure 6] FIG. 6 is a cross-sectional view showing an example of a thermally conductive sheet. [Figure 7] FIG. 7 is a cross-sectional view showing an example of a semiconductor device to which a thermally conductive sheet is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In this specification, the average particle size (D50) refers to the particle size at which the cumulative value of the cumulative curve of particle size values from the small particle size side of the particle size distribution is 50% when the entire particle size distribution is 100%. Note that the particle size distribution (particle size distribution) in this specification is determined on a volume basis. For example, a method of measuring the particle size distribution can be a method using a laser diffraction type particle size distribution measuring device.
[0013] <First embodiment of thermally conductive sheet> FIG. 1 is a cross-sectional view showing an example of a thermally conductive sheet 1 according to the present technology. The thermally conductive sheet 1 includes a first thermally conductive layer 2 containing a first binder resin 3, an anisotropic thermally conductive material 4, and a first inorganic filler 5, and a second thermally conductive layer 6 provided on both sides of the first thermally conductive layer 2, containing a second binder resin 7 and a second inorganic filler 8, having a thickness of more than 4 μm and less than 20 μm, and having a thermal conductivity of 0.8 W / (m·K) or more. The thermally conductive sheet 1 also has a developed area ratio of the surfaces 6A and 6B of the second thermally conductive layer 6 of 35% or less and a skewness of the surfaces 6A and 6B of the second thermally conductive layer 6 of -1.0 or less, as specified in ISO 25178, measured by a scanning white light interference microscope with an objective lens of 20 times.
[0014] Hereinafter, the thermal conductive sheet 1 shown in FIG. 1 will be described in detail as an example. The thermal conductive sheet 1 includes a second thermal conductive layer 6 having a thickness of more than 4 μm and less than 20 μm and a thermal conductivity of 0.8 W / (m·K) or more on both sides of the first thermal conductive layer 2. The thermal conductive sheet 1 also has a developed area ratio of the surfaces 6A, 6B of the second thermal conductive layer 6 of 35% or less, and the skewness of the surfaces 6A, 6B of the second thermal conductive layer 6 is -1.0 or less. This improves the smoothness of the surface of the thermal conductive sheet 1, and reduces the contact thermal resistance of the thermal conductive sheet 1, i.e., the contact thermal resistance value between the surface of the thermal conductive sheet 1 and the adherend. In this way, the thermal conductive sheet 1 has a good surface smoothness and can reduce the contact thermal resistance even if the film thickness is thin, and can reduce the thermal resistance value (particularly the thermal resistance value in a low load area) of the entire thermal conductive sheet 1 in a range of, for example, 0.5 mm or less.
[0015] The second thermally conductive layer 6 has a thickness of more than 4 μm, which effectively improves the smoothness of the surface of the thermally conductive sheet 1 and reduces the contact thermal resistance, thereby effectively reducing the thermal resistance value of the entire thermally conductive sheet 1. Furthermore, the second thermally conductive layer 6 has a thickness of less than 20 μm, which suppresses the influence of the magnitude of the thermal resistance value resulting from the thickness of the second thermally conductive layer 6 and effectively reduces the thermal resistance value of the entire thermally conductive sheet 1.
[0016] <Developed area ratio (Sdr)> The developed area ratio (Sdr) of the surfaces 6A, 6B of the second thermally conductive layer 6 in the thermally conductive sheet 1 is measured using a scanning white light interference microscope with an objective lens of 20x magnification in accordance with ISO 25178, and indicates how much the developed area (surface area) of a defined region has increased relative to the area of the defined region. For example, when the surfaces 6A, 6B of the second thermally conductive layer 6 are completely flat, the developed area ratio (Sdr) is 0%. The smaller the developed area ratio (Sdr) of the surfaces 6A, 6B of the second thermally conductive layer 6, the stronger the adhesion between the thermally conductive sheet 1 and the adherend.
[0017] Since the developed area ratio (Sdr) of the surfaces 6A, 6B of the second thermally conductive layer 6 of the thermally conductive sheet 1 is 35% or less, the surface of the thermally conductive sheet 1 has good smoothness, the contact thermal resistance can be reduced, and the thermal resistance value of the entire thermally conductive sheet 1 can be reduced.
[0018] In the thermally conductive sheet 1, the developed area ratio (Sdr) of the surfaces 6A and 6B of the second thermally conductive layer 6 may be 30% or less, 29% or less, 25% or less, 20% or less, or 18% or less. The lower limit of the developed area ratio (Sdr) of the surfaces 6A and 6B of the second thermally conductive layer 6 is not particularly limited, and may be, for example, 0% or more, 2% or more, 5% or more, 10% or more, or 15% or more. The developed area ratio (Sdr) of the surfaces 6A and 6B of the second thermally conductive layer 6 may be, for example, in the range of 0 to 35%, 16.54 to 32.18%, 16.54 to 29.90%, 16.54 to 28.12%, or 16.54 to 27.48%. In the thermally conductive sheet 1, it is most preferable that the developed area ratios (Sdr) of both surfaces 6A, 6B of the second thermally conductive layer 6 satisfy the above-mentioned range, but the developed area ratio (Sdr) of one of the surfaces 6A, 6B of the second thermally conductive layer 6 may satisfy the above-mentioned range. The developed area ratio (Sdr) of the surfaces 6A, 6B of the second thermally conductive layer 6 in the thermally conductive sheet 1 can be measured by the method described in the examples below.
[0019] <Skewness (Ssk)> The skewness (Ssk) of the surfaces 6A and 6B of the second thermally conductive layer 6 is measured by a scanning white light interference microscope with a 20x objective lens in accordance with ISO 25178, and is an index showing the degree of deviation of the height distribution from the average plane, in other words, the symmetry of the peaks (convex parts) and valleys (concave parts) based on the average plane of the surface of the thermally conductive sheet 1. When the skewness (Ssk) of the surface of the thermally conductive sheet 1 is 0, the height distribution is symmetrical up and down, in other words, the surface shape is symmetrical (normal distribution) with respect to the average plane. When the skewness (Ssk) of the surface of the thermally conductive sheet 1 exceeds 0, it indicates that the surface has many fine peaks, and the surface shape is biased downward (lower height side) with respect to the average plane. When the skewness (Ssk) of the surface of the thermally conductive sheet 1 is less than 0, it indicates that the surface has many fine valleys, and the surface shape is biased upward (higher height side) with respect to the average plane.
[0020] It is believed that the skewness (Ssk) of the surface of the thermally conductive sheet 1 is ideally 0. However, since the thermally conductive sheet 1 has a second thermally conductive layer 6 with a thickness of more than 4 μm and less than 20 μm and a thermal conductivity of 0.8 W / (m·K) or more on both sides of the first thermally conductive layer 2, the skewness (Ssk) of the surface is not usually 0. In addition, since the contact between the thermally conductive sheet 1 and the adherend is made on the surface of the thermally conductive sheet 1, when the skewness (Ssk) of the surface of the thermally conductive sheet 1 is negative, that is, when the skewness (Ssk) of the surface of the thermally conductive sheet 1 is less than 0 (especially -1.0 or less), it is considered that the effective contact area with the adherend is wider than when the skewness (Ssk) of the surface of the thermally conductive sheet 1 is close to 0. It is considered that the number of valleys on the surface of the thermally conductive sheet 1 does not depend on the increase or decrease of the skewness (Ssk) of the surface of the thermally conductive sheet 1.
[0021] FIG. 2 is a surface photograph of the thermally conductive sheet when the skewness of the surfaces 6A and 6B of the second thermally conductive layer 6 is -1.7, measured by a scanning white light interference microscope with a magnification of 20. FIG. 3 is a height histogram of the thermally conductive sheet 1 when the skewness of the surfaces 6A and 6B of the second thermally conductive layer 6 is -1.7. FIG. 4 is a surface photograph of the thermally conductive sheet when the skewness of the surface of the second thermally conductive layer is -0.63, measured by a scanning white light interference microscope with a magnification of 20. FIG. 5 is a height histogram of the thermally conductive sheet when the skewness of the surface of the second thermally conductive layer is -0.63. FIGS. 2 to 5 are the results for a 1 mm×1 mm area of the surface of the thermally conductive sheet, respectively. The thermally conductive sheet 1 of the present technology has a small developed area ratio (Sdr) of the surfaces 6A, 6B of the second thermally conductive layer 6 of 35% or less, and a skewness (Ssk) of the surfaces 6A, 6B of the second thermally conductive layer 6 of -1.0 or less, thereby improving the surface condition, for example, as shown in Figures 2 and 3, i.e., the smoothness of the surface of the thermally conductive sheet 1, and reducing the contact thermal resistance of the thermally conductive sheet 1.
[0022] Since the skewness (Ssk) of the surfaces 6A, 6B of the second thermally conductive layer 6 of the thermally conductive sheet 1 is -1.0 or less, the surface of the thermally conductive sheet 1 has good smoothness, the contact thermal resistance is reduced, and the thermal resistance value of the entire thermally conductive sheet 1 can be reduced.
[0023] In the thermally conductive sheet 1, the skewness (Ssk) of the surfaces 6A, 6B of the second thermally conductive layer 6 may be -1.1 or less, -1.2 or less, -1.3 or less, -1.4 or less, -1.5 or less, -1.6 or less, -1.7 or less, -1.8 or less, -1.9 or less, or -2.0 or less. The lower limit of the skewness (Ssk) of the surfaces 6A, 6B of the second thermally conductive layer 6 is not particularly limited, and may be, for example, -2.5 or more, or -2.0 or more. The skewness (Ssk) of the surface of the thermally conductive sheet 1 may be, for example, in the range of -1.00 to -1.91, in the range of -1.00 to -1.69, in the range of -1.00 to -1.51, in the range of -1.00 to -1.45, in the range of -1.00 to -1.23, or in the range of -1.23 to -1.91. It is most preferable that the skewness (Ssk) of both surfaces 6A and 6B of the second thermally conductive layer 6 of the thermally conductive sheet 1 satisfy the above-mentioned range, but the skewness (Ssk) of one of the surfaces 6A and 6B of the second thermally conductive layer 6 may satisfy the above-mentioned range. The skewness (Ssk) of the surface of the thermally conductive sheet 1 can be measured by a method described in the examples below.
[0024] In this way, the thermally conductive sheet 1 has a thickness of the second thermally conductive layer 6 that is more than 4 μm and less than 20 μm, a thermal conductivity of 0.8 W / (m·K) or more, and the developed area ratio of the surfaces 6A, 6B of the second thermally conductive layer 6 that is specified in ISO 25178 and measured with a scanning white light interference microscope with an objective lens of 20 times is 35% or less, and the skewness of the surfaces 6A, 6B of the second thermally conductive layer 6 is -1.0 or less, so that the area from the surface of the thermally conductive sheet 1 to about 20 μm is wider, and the contact efficiency with the adherend is improved. As a result, even if the thermally conductive sheet 1 has a thin film thickness, the contact thermal resistance can be reduced, and the thermal resistance value of the entire thermally conductive sheet 1 can be reduced.
[0025] <Arithmetic mean height (Sa)> The arithmetic mean height (Sa) of the surface of the thermal conductive sheet 1 (surfaces 6A and 6B of the second thermal conductive layer 6) is measured by a scanning white light interference microscope with an objective lens of 20 times magnification, and is measured according to ISO 25178, and represents the average of the absolute values of the differences in height at each point with respect to the average plane of the surface. The arithmetic mean height (Sa) of the surfaces 6A and 6B of the second thermal conductive layer 6 is 7.0 μm or less, and may be 6.0 μm or less. The lower limit of the arithmetic mean height (Sa) of the surfaces 6A and 6B of the second thermal conductive layer 6 is not particularly limited, and may be, for example, 1.0 μm or more, or 2.0 μm or more. The arithmetic mean height (Sa) of the surfaces 6A and 6B of the second thermal conductive layer 6 may be, for example, in the range of 3.56 to 5.46 μm, or in the range of 3.56 to 4.92 μm. In the thermally conductive sheet 1, it is most preferable that the arithmetic mean heights (Sa) of both surfaces 6A, 6B of the second thermally conductive layer 6 satisfy the above-mentioned range, but the arithmetic mean height (Sa) of one of the surfaces 6A, 6B of the second thermally conductive layer 6 may satisfy the above-mentioned range. The arithmetic mean height (Sa) of the surface of the thermally conductive sheet 1 can be measured by the method described in the examples below.
[0026] <Thermal resistance value> The thermal conductive sheet 1 has a thermal conductivity of 0.3 kgf / cm2 as measured by a method in accordance with ASTM-D5470. 2 The lower the thermal resistance value when pressure is applied, the more preferable. In this specification, when the term "thermal resistance value" is used, it is synonymous with the thermal resistance of the entire thermally conductive sheet 1 described above, and refers to the combined thermal contact resistance and thermal resistance of the thermally conductive sheet 1 itself. For example, when the thermally conductive sheet 1 has a thickness of 0.3 mm, the thermal resistance value is 0.3 kgf / cm 2 Thermal resistance when pressurized is 0.31℃ cm 2 / W, and preferably less than 0.30°C cm 2 / W or less, 0.29°C cm 2 / W or less, and 0.28°C cm 2 / W or less, and 0.27°C cm 2 / W or less. 2The lower limit of the thermal resistance when pressurized is not particularly limited, but a lower value is preferable, and 0°C cm 2 / W, e.g., 0.05°C cm 2 / W or more. When the thickness of the thermally conductive sheet 1 is 0.3 mm, the thermal conductivity is 0.3 kgf / cm 2 Thermal resistance when pressurized is 0.25 to 0.30°C cm 2 / W, and may range from 0.25 to 0.27 °C cm 2 / W range.
[0027] The thermal conductive sheet 1 has a thermal conductivity of 0.5 kgf / cm2 measured by a method in accordance with ASTM-D5470. 2 The lower the thermal resistance value when pressure is applied, the more preferable. For example, when the thermal conductive sheet 1 has a thickness of 0.3 mm, the thermal resistance value is 0.5 kgf / cm 2 Thermal resistance when pressurized is 0.31℃ cm 2 / W, and preferably less than 0.30°C cm 2 / W or less, 0.29°C cm 2 / W or less, and 0.28°C cm 2 / W or less, and 0.27°C cm 2 / W or less, and 0.26°C cm 2 / W or less, and 0.25°C cm 2 / W or less, and 0.24°C cm 2 / W or less, and 0.23°C cm 2 / W or less. 2 The lower limit of the thermal resistance when pressurized is not particularly limited, but a lower value is preferable, and 0°C cm 2 / W, e.g., 0.05°C cm 2 / W or more. When the thickness of the thermally conductive sheet 1 is 0.3 mm, the thermal conductivity can be 0.5 kgf / cm 2 Thermal resistance when pressurized is 0.22 to 0.30°C cm 2 / W, and may be in the range of 0.22 to 0.23 °C cm 2 / W range.
[0028] <Tack strength> The thermally conductive sheet 1 can reduce the contact thermal resistance and has good adhesion and tackiness. With regard to the tackiness, the thermally conductive sheet 1 may have a tackiness (hereinafter simply referred to as "tackiness") of 21 gf or more, 50 gf or more, 52 gf or more, 67 gf or more, 69 gf or more, or 84 gf or more when a probe having a diameter of 5.1 mm is pressed into the thermally conductive sheet 1 at 2 mm / sec to a depth of 50 μm and pulled out at 10 mm / sec. The upper limit of the tackiness of the thermally conductive sheet 1 is not particularly limited, but from the viewpoint of achieving both a reduction in the contact thermal resistance and good tackiness, it may be, for example, 100 gf or less, or 84 gf or less. The tackiness of the thermally conductive sheet 1 may be in the range of 50 to 84 gf. The tackiness of the thermally conductive sheet 1 can be measured by a method described in the examples described later.
[0029] The thickness of the thermally conductive sheet 1, i.e., the sum of the thickness of the first thermally conductive layer 2 and the thickness of the second thermally conductive layer 6, can be appropriately selected according to the purpose, and can be, for example, 0.05 mm or more, 0.1 mm or more, 0.2 mm or more, or 0.3 mm or more. The upper limit of the thickness of the thermally conductive sheet 1 can be, for example, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, 1 mm or less, or 0.5 mm or less. As described above, even if the thermally conductive sheet 1 according to the present technology has a thin film thickness, for example, in the range of 0.5 mm or less, the contact thermal resistance can be reduced, and the thermal resistance value of the entire thermally conductive sheet 1 (particularly, the thermal resistance value in the low load region) can be reduced. The thickness of the thermally conductive sheet 1 can be calculated, for example, by measuring the thickness B of the thermally conductive sheet 1 at any five points and calculating the arithmetic average value.
[0030] <First thermal conductive layer> Next, a description will be given of the first thermally conductive layer 2 constituting the thermally conductive sheet 1. The first thermally conductive layer 2 contains a first binder resin 3, an anisotropic thermally conductive material 4 and a first inorganic filler 5.
[0031] <First binder resin> The first binder resin 3 is for holding the anisotropic thermally conductive material 4 and the first inorganic filler 5 in the first thermally conductive layer 2. The first binder resin 3 is selected according to the properties required for the first thermally conductive layer 2, such as mechanical strength, heat resistance, and electrical properties. The first binder resin 3 can be selected from among thermoplastic resins, thermoplastic elastomers, and thermosetting resins.
[0032] Examples of thermoplastic resins include polyethylene, polypropylene, ethylene-α-olefin copolymers such as ethylene-propylene copolymers, polymethylpentene, polyvinyl chloride, polyvinylidene chloride, polyvinyl acetate, ethylene-vinyl acetate copolymers, polyvinyl alcohol, polyvinyl acetal, fluorine-based polymers such as polyvinylidene fluoride and polytetrafluoroethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polystyrene, polyacrylonitrile, styrene-acrylonitrile copolymers, acrylonitrile-butadiene-styrene copolymer (ABS) resins, polyphenylene-ether copolymers (PPE) resins, modified PPE resins, aliphatic polyamides, aromatic polyamides, polyimides, polyamideimides, polymethacrylic acid, polymethacrylic acid esters such as polymethacrylic acid methyl ester, polyacrylic acids, polycarbonates, polyphenylene sulfide, polysulfones, polyether sulfones, polyether nitriles, polyether ketones, polyketones, liquid crystal polymers, and ionomers.
[0033] Examples of the thermoplastic elastomer include a styrene-butadiene block copolymer or a hydrogenated product thereof, a styrene-isoprene block copolymer or a hydrogenated product thereof, a styrene-based thermoplastic elastomer, an olefin-based thermoplastic elastomer, a vinyl chloride-based thermoplastic elastomer, a polyester-based thermoplastic elastomer, a polyurethane-based thermoplastic elastomer, and a polyamide-based thermoplastic elastomer.
[0034] Examples of the thermosetting resin include crosslinked rubber, epoxy resin, phenol resin, polyimide resin, unsaturated polyester resin, diallyl phthalate resin, addition reaction type silicone resin, condensation reaction type silicone resin, etc. Specific examples of the crosslinked rubber include natural rubber, acrylic rubber, butadiene rubber, isoprene rubber, styrene-butadiene copolymer rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene-propylene copolymer rubber, chlorinated polyethylene rubber, chlorosulfonated polyethylene rubber, butyl rubber, halogenated butyl rubber, fluororubber, urethane rubber, and silicone rubber.
[0035] As the first binder resin 3, for example, a silicone resin is preferable from the viewpoint of adhesion between the heat generating surface of a heat generating body (for example, an electronic component) and the heat sink surface, and from the viewpoint of adhesion with the second thermally conductive layer 6. As the silicone resin, for example, a two-liquid addition reaction type silicone resin can be used, which is mainly composed of silicone (polyorganosiloxane) having an alkenyl group, a base agent containing a curing catalyst, and a curing agent having a hydrosilyl group (Si-H group). As the silicone having an alkenyl group, a polyorganosiloxane having at least two alkenyl groups in one molecule can be used. As an example, a polyorganosiloxane having a vinyl group can be used. The curing catalyst is a catalyst for promoting the addition reaction between the alkenyl group in the silicone having an alkenyl group and the hydrosilyl group in the curing agent having a hydrosilyl group. Examples of the curing catalyst include catalysts well known as catalysts used in hydrosilylation reactions, such as platinum group curing catalysts, such as platinum group metals such as platinum, rhodium, and palladium, platinum chloride, and complexes of platinum and organic compounds. Examples of the curing agent having a hydrosilyl group include polyorganosiloxanes having a hydrosilyl group (organohydrogenpolysiloxanes having at least two hydrogen atoms directly bonded to silicon atoms in one molecule).
[0036] When the above-mentioned two-component addition reaction type silicone resin is used as the first binder resin 3, for example, the ratio of the main component (silicone main component) to the curing agent component, i.e., the mixing ratio of the polyorganosiloxane having a vinyl group and the polyorganosiloxane having a hydrosilyl group, is not particularly limited, and can be set to a mixing ratio in the range of 0.3 to 0.9 mol of hydrosilyl groups per 1 mol of vinyl groups.
[0037] The content of the first binder resin 3 in the first thermally conductive layer 2 is not particularly limited and can be appropriately selected according to the purpose. For example, the content of the first binder resin 3 in the first thermally conductive layer 2 can be 20 volume % or more, may be 24 volume % or more, may be 28 volume % or more, may be 30 volume % or more, or may be 32 volume % or more. The upper limit of the content of the first binder resin 3 in the first thermally conductive layer 2 can be 60 volume % or less, may be 50 volume % or less, or may be 45 volume % or less. The content of the first binder resin 3 in the first thermally conductive layer 2 can be, for example, in the range of 20 to 40 volume %. The first binder resin 3 may be used alone or in combination of two or more types. When two or more types of the first binder resin 3 are used in combination, it is preferable that the total amount thereof satisfies the above-mentioned content.
[0038] <Anisotropic heat conductive materials> The anisotropic heat conductive material 4 is a heat conductive material having anisotropy in shape. For example, an example of the anisotropic heat conductive material 4 is a heat conductive filler having a long axis and a short axis, and a specific example is a fibrous filler. The fibrous filler, which is an example of the anisotropic heat conductive material 4, is not particularly limited as long as it is fibrous and has the necessary heat conductivity, and examples thereof include carbon fiber and aluminum nitride whisker. In the following, a detailed description will be given of an example in which carbon fiber is used as the anisotropic heat conductive material 4. The anisotropic heat conductive material 4 includes a shape having a long axis and a short axis, the lengths of the long axis and the short axis are different, and the aspect ratio (average long axis length / average short axis length) exceeds 1. The anisotropic heat conductive material 4 may be used alone or in combination of two or more types.
[0039] Examples of the carbon fiber that can be used include pitch-based carbon fiber, PAN-based carbon fiber, carbon fiber obtained by graphitizing PBO fiber, and carbon fiber synthesized by arc discharge, laser evaporation, CVD (chemical vapor deposition), CCVD (catalytic chemical vapor deposition), etc. Among these, pitch-based carbon fiber is preferred from the viewpoint of thermal conductivity.
[0040] The average fiber length (average major axis length) of the anisotropic heat conductive material 4 can be, for example, 50 to 250 μm, and may be 75 to 220 μm. The average fiber diameter (average minor axis length) of the anisotropic heat conductive material 4 can be appropriately selected depending on the purpose, and may be, for example, 4 to 20 μm. The aspect ratio of the anisotropic heat conductive material 4 can be appropriately selected depending on the purpose, and may be, for example, 8 or more, and may be in the range of 9 to 30, from the viewpoint of thermal conductivity. The average major axis length and average minor axis length of the anisotropic heat conductive material 4 can be measured, for example, by a microscope or a scanning electron microscope (SEM).
[0041] The anisotropic thermally conductive material 4 is preferably oriented in the thickness direction in the first thermally conductive layer 2. Here, the anisotropic thermally conductive material 4 being oriented in the thickness direction in the first thermally conductive layer 2 means, for example, that the proportion of the anisotropic thermally conductive material 4 having its major axis oriented in the thickness direction of the first thermally conductive layer 2 (thickness direction B of the thermally conductive sheet 1 shown in FIG. 1 ) among all the anisotropic thermally conductive materials 4 in the first thermally conductive layer 2 is 50% or more, may be 55% or more, may be 60% or more, may be 65% or more, may be 70% or more, may be 80% or more, may be 90% or more, may be 95% or more, or may be 99% or more. The long axis of the anisotropic thermally conductive material 4 being oriented in the thickness direction of the first thermally conductive layer 2 means, for example, that the long axis of the anisotropic thermally conductive material 4 is in the range of 60 to 120 degrees, 70 to 100 degrees, or 90 degrees (approximately perpendicular) relative to the surface direction of the first thermally conductive layer 2 (surface direction A of the thermally conductive sheet 1 shown in Figure 1).
[0042] The content of the anisotropic heat conductive material 4 in the first heat conductive layer 2 can be, for example, 5 vol% or more, 10 vol% or more, 14 vol% or more, 20 vol% or more, 22 vol% or more, 24 vol% or more, or 26 vol% or more, from the viewpoint of the thermal conductivity of the heat conductive sheet 1. The content of the anisotropic heat conductive material 4 in the first heat conductive layer 2 can be, for example, 30 vol% or less, or 28 vol% or less, from the viewpoint of the formability of the first heat conductive layer 2. The content of the anisotropic heat conductive material 4 in the first heat conductive layer 2 can be, for example, in the range of 26 to 30 vol%, or can be in the range of 27 to 29 vol%. When two or more kinds of anisotropic heat conductive materials 4 are used in combination, it is preferable that the total amount thereof satisfies the above-mentioned content.
[0043] <The first inorganic filler> The first inorganic filler 5 is an inorganic filler other than the anisotropic thermally conductive material 4. The first inorganic filler 5 includes, for example, a thermally conductive filler in a spherical shape, a powder shape, a granular shape, or the like. From the viewpoint of the thermal conductivity of the thermally conductive sheet 1, the material of the first inorganic filler 5 is preferably, for example, a ceramic filler, and specific examples thereof include aluminum oxide (alumina, sapphire), aluminum nitride, aluminum, aluminum hydroxide, and boron nitride. The first inorganic filler 5 may be used alone or in combination of two or more kinds. For example, two or more kinds of thermally conductive fillers having different average particle sizes may be used in combination as the first inorganic filler 5.
[0044] In particular, taking into consideration the thermal conductivity of the thermal conductive sheet 1 and the specific gravity of the thermal conductive sheet 1, it is preferable for the first inorganic filler 5 to contain at least one of aluminum oxide and aluminum nitride, and it is more preferable to use aluminum oxide and aluminum nitride in combination.
[0045] The average particle size of the aluminum oxide can be, for example, in the range of 0.1 to 10 μm, or may be in the range of 0.1 to 8 μm, or may be in the range of 0.1 to 7 μm, or may be in the range of 0.1 to 3 μm, from the viewpoint of the specific gravity of the thermal conductive sheet 1. The average particle size of the aluminum nitride can be, for example, in the range of 0.1 to 10 μm, or may be in the range of 0.5 to 5 μm, or may be in the range of 0.5 to 3 μm, or may be in the range of 0.5 to 2 μm, from the viewpoint of the specific gravity of the thermal conductive sheet 1.
[0046] The content of the first inorganic filler 5 in the first thermally conductive layer 2 can be appropriately selected depending on the purpose. The content of the first inorganic filler 5 in the first thermally conductive layer 2 can be, for example, 10 vol% or more, 15 vol% or more, 20 vol% or more, 25 vol% or more, 30 vol% or more, 35 vol% or more, or 39 vol% or more. The upper limit of the content of the first inorganic filler 5 in the first thermally conductive layer 2 can be, for example, 55 vol% or less, 50 vol% or less, 49 vol% or less, 45 vol% or less, or 40 vol% or less. The content of the first inorganic filler 5 in the first thermally conductive layer 2 can be, for example, in the range of 35 to 45 vol% or in the range of 37 to 43 vol%. When two or more types of the first inorganic filler 5 are used in combination, it is preferable that the total amount thereof satisfies the above-mentioned content.
[0047] For example, when aluminum oxide and aluminum nitride are used in combination as the first inorganic filler 5, the content of aluminum nitride in the first thermal conductive layer 2 can be in the range of 10 to 35 volume % and the content of aluminum oxide can be in the range of 5 to 25 volume %, or the content of aluminum nitride can be in the range of 20 to 30 volume % and the content of aluminum oxide can be in the range of 10 to 20 volume %.
[0048] As a specific example of the first thermally conductive layer 2, it is preferable that the content of the first binder resin 3 in the first thermally conductive layer 2 is 20 to 40 volume % and the total content of the anisotropic thermally conductive material 4 and the first inorganic filler 5 is 60 to 80 volume %.
[0049] The first thermally conductive layer 2 may further contain other components in addition to the first binder resin 3, the anisotropic thermally conductive material 4, and the first inorganic filler 5, within a range that does not impair the effects of the present technology. Examples of the other components include coupling agents, dispersants, curing accelerators, retarders, tackifiers, plasticizers, flame retardants, antioxidants, stabilizers, colorants, and solvents. For example, the first thermally conductive layer 2 may use an anisotropic thermally conductive material 4 treated with a coupling agent and / or a first inorganic filler 5 treated with a coupling agent in order to further improve the dispersibility of the anisotropic thermally conductive material 4 and the first inorganic filler 5.
[0050] The hardness of the first thermally conductive layer 2 is preferably in the range of 20 to 90 in Shore type OO hardness, and may be in the range of 30 to 80, 50 to 75, 55 to 75, 65 to 75, or 60 to 75. When the hardness of the first thermally conductive layer 2 is in such a range, the thermally conductive sheet 1 can better conform to the adherend, and the adherend and the thermally conductive sheet 1 can more easily come into surface contact with each other, thereby more effectively exerting thermal conductivity. The hardness of the first thermally conductive layer 2 can be measured by the method described in the examples below.
[0051] The thickness of the first thermally conductive layer 2 is not particularly limited and can be appropriately selected depending on the purpose, and can be, for example, 0.05 mm or more, 0.1 mm or more, 0.2 mm or more, or 0.3 mm or more. The upper limit of the thickness of the first thermally conductive layer 2 can be, for example, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, 1 mm or less, or 0.5 mm or less. The thickness of the first thermally conductive layer 2 can be determined, for example, by measuring the thickness of the first thermally conductive layer 2 at any five points and taking the arithmetic average value.
[0052] <Second heat conductive layer> Next, the second thermally conductive layer 6 constituting the thermally conductive sheet 1 will be described. As described above, the second thermally conductive layer 6 has a thickness of more than 4 μm and less than 20 μm. In addition, the second thermally conductive layer 6 is preferably provided on almost the entire surface of both sides of the first thermally conductive layer 2, and more preferably provided on the entire surface of both sides of the first thermally conductive layer 2. The second thermally conductive layer 6 contains a second binder resin 7 and a second inorganic filler 8. In the thermally conductive sheet 1, the two second thermally conductive layers 6 may have the same configuration or different configurations.
[0053] <Second binder resin> The second binder resin 7 is synonymous with the first binder resin 3 in the above-mentioned first thermally conductive layer 2. When, for example, a two-liquid type addition reaction type silicone resin is used as the second binder resin 7, the ratio of the main component (silicone main component) to the curing component, i.e., the mixing ratio of the polyorganosiloxane having a vinyl group and the polyorganosiloxane having a hydrosilyl group, is preferably in the range of 0.54 to 0.84 mol of hydrosilyl groups per 1 mol of vinyl groups, from the viewpoint of improving the tackiness of the thermally conductive sheet 1, and may be in the range of 0.54 to 0.70 mol.
[0054] Furthermore, from the viewpoint of improving the tackiness of the thermally conductive sheet 1, when the second binder resin 7 is an addition curing silicone resin, the penetration according to JIS K 2220 measured on the addition curing silicone resin alone is preferably 6 to 85, or may be 30 to 85, or may be 40 to 80.
[0055] The content of the second binder resin 7 in the second thermally conductive layer 6 is not particularly limited and can be appropriately selected according to the purpose. For example, the content of the second binder resin 7 in the second thermally conductive layer 6 can be 35 vol% or more, may be 40 vol% or more, or may be 42 vol% or more. The upper limit of the content of the second binder resin 7 in the second thermally conductive layer 6 can be 55 vol% or less, may be 50 vol% or less, or may be 48 vol% or less. The content of the second binder resin 7 in the second thermally conductive layer 6 can be, for example, in the range of 35 to 50 vol%. The second binder resin 7 may be used alone or in combination of two or more types. When two or more types of the second binder resins 7 are used in combination, it is preferable that the total amount satisfies the above-mentioned content.
[0056] Other than that, the preferred conditions and ranges of the second binder resin 7 are similar to those of the first binder resin 3 in the first thermally conductive layer 2 described above.
[0057] <Second inorganic filler> The second inorganic filler 8 is an inorganic filler, and includes, for example, a thermally conductive filler in a spherical shape, a powder shape, a granular shape, etc. The second inorganic filler 8 may also include a thermally conductive filler having anisotropic shape, like the anisotropic thermally conductive material 4 described above.
[0058] The content of the second inorganic filler 8 in the second thermally conductive layer 6 can be appropriately selected depending on the purpose. The content of the second inorganic filler 8 in the second thermally conductive layer 6 can be, for example, 10 vol% or more, 15 vol% or more, 20 vol% or more, 25 vol% or more, 30 vol% or more, 35 vol% or more, 40 vol% or more, or 45 vol% or more. The upper limit of the content of the second inorganic filler 8 in the second thermally conductive layer 6 can be, for example, 65 vol% or less, 60 vol% or less, 55 vol% or less, or 53 vol% or less. The content of the second inorganic filler 8 in the second thermally conductive layer 6 can be, for example, in the range of 35 to 65 vol%, 40 to 60 vol%, or 50 to 65 vol%. When two or more types of second inorganic fillers 8 are used in combination, it is preferable that the total amount thereof satisfies the above-mentioned content.
[0059] When, for example, aluminum oxide and aluminum nitride are used in combination as the second inorganic filler 8, the content of aluminum nitride in the second thermal conductive layer 6 can be in the range of 10 to 40 volume % and the content of aluminum oxide can be in the range of 5 to 35 volume %, or the content of aluminum nitride can be in the range of 25 to 35 volume % and the content of aluminum oxide can be in the range of 15 to 25 volume %.
[0060] Otherwise, second inorganic filler 8 is similar to first inorganic filler 5 and anisotropic thermally conductive material 4 in first thermally conductive layer 2 described above.
[0061] As a specific example of the second thermally conductive layer 6, it is preferable that the content of the second binder resin 7 in the second thermally conductive layer 6 is 35 to 50 volume % and the content of the second inorganic filler 8 is 50 to 65 volume %.
[0062] The second thermally conductive layer 6 may further contain other components in addition to the second binder resin 7 and the second inorganic filler 8, as long as the effect of the present technology is not impaired. Examples of the other components include coupling agents, dispersants, curing accelerators, retarders, tackifiers, plasticizers, flame retardants, antioxidants, stabilizers, colorants, and solvents. For example, the second thermally conductive layer 6 may use the second inorganic filler 8 treated with a coupling agent in order to further improve the dispersibility of the second inorganic filler 8.
[0063] The second thermally conductive layer 6 has a thermal conductivity of 0.8 W / (m·K) or more, specifically, the thermal conductivity in the thickness direction (thickness direction B of the thermally conductive sheet 1) of the second thermally conductive layer 6 is preferably 0.8 W / (m·K) or more, may be 0.9 W / (m·K) or more, may be 1.0 W / (m·K) or more, and may be in the range of 0.8 to 2.0 W / (m·K). The thermal conductivity of the second thermally conductive layer 6 can be measured by the method described in the examples below.
[0064] As described above, the thermally conductive sheet 1 includes the first thermally conductive layer 2 containing the first binder resin 3, the anisotropic thermally conductive material 4, and the first inorganic filler 5, and the second thermally conductive layer 6 provided on both sides of the first thermally conductive layer 2, containing the second binder resin 7 and the second inorganic filler 8, having a thickness of more than 4 μm and less than 20 μm, and having a thermal conductivity of 0.8 W / (m·K) or more. The thermally conductive sheet 1 also has a developed area ratio of the surfaces 6A and 6B of the second thermally conductive layer 6 of 35% or less and a skewness of the surfaces 6A and 6B of the second thermally conductive layer 6 of -1.0 or less, as specified in ISO 25178, measured by a scanning white light interference microscope with an objective lens of 20x. A thermally conductive sheet 1 having such a configuration has good surface smoothness, and even though it is thin, it can reduce contact thermal resistance and reduce the thermal resistance value of the entire thermally conductive sheet 1 (especially the thermal resistance value in the low load area).
[0065] The thermally conductive sheet 1 may further include layers other than the first thermally conductive layer 2 and the second thermally conductive layer 6, or may not include any other layers, as long as the effects of the present technology are not impaired. For example, the thermally conductive sheet 1 may further include another layer between the first thermally conductive layer 2 and the second thermally conductive layer 6.
[0066] <Second embodiment of thermally conductive sheet> Fig. 6 is a cross-sectional view showing an example of a thermally conductive sheet. The thermally conductive sheet 10 shown in Fig. 6 includes a second thermally conductive layer 6 having a thickness of more than 4 µm and less than 20 µm and a thermal conductivity of 0.8 W / (m·K) or more on one side of a first thermally conductive layer 2. The thermally conductive sheet 10 has a developed area ratio of a surface 6A of the second thermally conductive layer 6 of 35% or less and a skewness of the surface 6A of the second thermally conductive layer 6 of -1.0 or less as defined in ISO 25178, measured by a scanning white light interference microscope (white light interferometer) with an objective lens of 20x magnification.
[0067] As shown in Fig. 6, for example, when the second thermally conductive layer 6 is provided only on one side of the first thermally conductive layer 2, it is possible to provide a difference in tack strength between both sides of the thermally conductive sheet 10. In this case, for example, during mounting, one side can be left fixed to the heat generating body, and the other side can be fixed after aligning the heat sink by repeatedly contacting and removing it from the thermally conductive sheet 10, thereby improving the convenience of mounting the thermally conductive sheet 10. Furthermore, compared to a case where the second thermally conductive layer 6 is not provided, the thermally conductive sheet 10 also has the effect of reducing the thermal resistance value.
[0068] <Method of manufacturing thermally conductive sheet> The thermally conductive sheet 1 according to the present technology can be obtained, for example, by the following manufacturing method. That is, the manufacturing method of the thermally conductive sheet 1 includes, for example, a step of forming a first thermally conductive layer 2 containing a first binder resin 3, an anisotropic thermally conductive material 4, and a first inorganic filler 5 (hereinafter also referred to as step A), and a step of forming a second thermally conductive layer 6 containing a second binder resin 7 and a second inorganic filler 8, having a thickness of more than 4 μm and less than 20 μm, and having a thermal conductivity of 0.8 W / (m·K) or more on both sides of the first thermally conductive layer 2 (hereinafter also referred to as step B). Moreover, the thermally conductive sheet 1 obtained by such a manufacturing method has a developed area ratio of the surfaces 6A and 6B of the second thermally conductive layer 6 of 35% or less and a skewness of the surfaces 6A and 6B of the second thermally conductive layer 6 of -1.0 or less as specified in ISO 25178, as measured by a scanning white light interference microscope with an objective lens of 20 times. An example of a method for producing the thermally conductive sheet 1 shown in FIG. 1 will now be described.
[0069] <Process A> In step A, a first thermally conductive layer 2 containing a first binder resin 3, an anisotropic thermally conductive material 4, and a first inorganic filler 5 is formed. In one example of step A, first, the anisotropic thermally conductive material 4 and the first inorganic filler 5 are dispersed in the first binder resin 3 to prepare a first thermally conductive composition containing the first binder resin 3, the anisotropic thermally conductive material 4, and the first inorganic filler 5. The first thermally conductive composition can be prepared by uniformly mixing the first binder resin 3, the anisotropic thermally conductive material 4, the first inorganic filler 5, and, if necessary, the other components described above, by a known method.
[0070] Next, the first thermally conductive composition is extruded and then cured to obtain a columnar cured product (first thermally conductive molded product). The method of extrusion is not particularly limited, and can be appropriately selected from various known extrusion methods according to the viscosity of the first thermally conductive composition and the properties required for the thermally conductive sheet 1 and the first thermally conductive layer 2. In the extrusion method, when the first thermally conductive composition is extruded from a die, the first binder resin 3 in the first thermally conductive composition flows, and the anisotropic thermally conductive material 4 is oriented along the flow direction. The size and shape of the columnar cured product can be determined according to the desired size of the thermally conductive sheet 1. For example, a rectangular parallelepiped with a cross-sectional vertical size of 0.5 to 15 cm and a horizontal size of 0.5 to 15 cm can be mentioned. The length of the rectangular parallelepiped can be determined as needed.
[0071] Next, the first thermally conductive molded body is cut into a sheet to obtain a first thermally conductive layer 2 (sheet-shaped molded body). For example, a columnar cured product is cut to a predetermined thickness in the length direction of the column to obtain the first thermally conductive layer 2. The anisotropic thermally conductive material 4 is exposed on the surface (cut surface) of the first thermally conductive layer 2. The cutting method of the first thermally conductive molded body is not particularly limited, and can be appropriately selected from known slicing devices depending on the size and mechanical strength of the first thermally conductive molded body. When an extrusion molding method is used to obtain the first thermally conductive molded body, the anisotropic thermally conductive material 4 may be oriented in the extrusion direction, so the cutting direction of the first thermally conductive molded body is preferably 60 to 120 degrees, more preferably 70 to 100 degrees, and even more preferably 90 degrees (approximately perpendicular) to the extrusion direction. The cutting direction of the first thermally conductive molded body is not particularly limited other than the above, and can be appropriately selected depending on the purpose of use of the thermally conductive sheet 1, etc. As described above, the hardness of the first thermally conductive layer 2 is preferably in the range of 20 to 90 in Shore type OO hardness, for example.
[0072] <Process B> In step B, a second thermally conductive layer 6 containing a second binder resin 7 and a second inorganic filler 8, having a thickness of more than 4 μm and less than 20 μm, and having a thermal conductivity of 0.8 W / (m·K) or more is formed on both sides of the first thermally conductive layer 2. In one example of step B, first, a second thermally conductive composition containing the second binder resin 7 and the second inorganic filler 8 is prepared by dispersing the second inorganic filler 8 in the second binder resin 7. The second thermally conductive composition can be prepared by uniformly mixing the second binder resin 7, the second inorganic filler 8, and, if necessary, the other components described above, by a known method.
[0073] Next, a second thermally conductive composition is applied onto the first thermally conductive layer 2 to a thickness of more than 4 μm and less than 20 μm, and cured to obtain a thermally conductive sheet 1 having a second thermally conductive layer 6 having a thickness of more than 4 μm and less than 20 μm and a thermal conductivity of 0.8 W / (m·K) or more.
[0074] For example, the second thermally conductive composition can be applied to a substrate film that has been subjected to a release treatment to a thickness of more than 4 μm and less than 20 μm, and the substrate film to which the second thermally conductive composition has been applied can be transferred to both sides of the first thermally conductive layer 2 to coat them. Thereafter, the second thermally conductive composition can be cured and the substrate film can be peeled off, thereby forming the second thermally conductive layer 6 on both sides of the first thermally conductive layer 2.
[0075] In addition, the second thermally conductive layer 6 can be formed on at least a portion of both sides of the first thermally conductive layer 2 by transferring and coating a substrate film coated with the second thermally conductive composition onto both sides of the first thermally conductive layer 2, then curing the second thermally conductive composition and peeling off the substrate film.
[0076] The second thermally conductive composition can be cured, for example, at 80° C. for 6 hours.
[0077] In this manner, in step B, the second thermally conductive layer 6 containing the second binder resin 7 and the second inorganic filler 8, having a thickness of more than 4 μm and less than 20 μm, and having a thermal conductivity of 0.8 W / (m·K) or more can be formed on both sides of the first thermally conductive layer 2.
[0078] According to the above-described manufacturing method, the above-described thermally conductive sheet 1 can be obtained, that is, a thermally conductive sheet 1 having a second thermally conductive layer 6 with a thickness of more than 4 μm and less than 20 μm and a thermal conductivity of 0.8 W / (m·K) or more on both sides of a first thermally conductive layer 2, in which the developed area ratio of the surfaces 6A, 6B of the second thermally conductive layer 6 is 35% or less and the skewness of the surfaces 6A, 6B of the second thermally conductive layer 6 is -1.0 or less, as defined in ISO 25178, as measured with a scanning white light interference microscope with an objective lens of 20x.
[0079] As described above, the thermally conductive sheet 1 obtained by this manufacturing method has a good surface smoothness, and even if the film thickness is thin, the contact thermal resistance can be reduced, and the thermal resistance value of the entire thermally conductive sheet 1 (particularly the thermal resistance value in a low load region) can be reduced. Therefore, the manufacturing method of the thermally conductive sheet 1 does not need to include any further steps other than step A and step B, such as a step of pressing the thermally conductive sheet or a step of polishing the surface of the thermally conductive sheet. Therefore, the manufacturing method of the thermally conductive sheet 1 can obtain a thermally conductive sheet 1 with reduced contact thermal resistance and reduced thermal resistance value even if the film thickness is thin, with fewer steps.
[0080] In the method for producing the thermally conductive sheet 1, step A may be performed before step B or in parallel with step B. When producing the thermally conductive sheet 10 shown in FIG. 6, the second thermally conductive layer 6 may be formed on only one side of the first thermally conductive layer 2 in step B.
[0081] <Electronic equipment> For example, the thermally conductive sheet 1 can be disposed between a heat generating body and a heat sink to form an electronic device (thermal device) having a structure in which the sheet is disposed between the heat generating body and the heat sink to dissipate heat generated by the heat generating body. The electronic device has at least the heat generating body, the heat sink, and the thermally conductive sheet 1, and may further have other members as necessary. In this way, the electronic device to which the thermally conductive sheet 1 is applied has the thermally conductive sheet 1 sandwiched between the heat generating body and the heat sink, so that the thermally conductive sheet 1 has excellent adhesion to the heat generating body while realizing high thermal conductivity by the thermally conductive sheet 1, and excessive bleeding of the binder resin (the first binder resin 3 and the second binder resin 7) from the thermally conductive sheet 1 can be suppressed.
[0082] In particular, as described above, electronic devices to which the thermally conductive sheet 1 is applied have excellent surface smoothness of the thermally conductive sheet 1, and even if the thickness of the thermally conductive sheet 1 is thin, the contact thermal resistance of the thermally conductive sheet 1 can be reduced, and the thermal resistance value of the entire thermally conductive sheet 1 (particularly the thermal resistance value in the low load area) can be reduced.
[0083] The heat generating body is not particularly limited, and examples thereof include electronic components that generate heat in an electric circuit, such as integrated circuit elements such as a CPU, a GPU (Graphics Processing Unit), a DRAM (Dynamic Random Access Memory), and a flash memory, as well as transistors, resistors, etc. Heat generating bodies also include components that receive optical signals, such as optical transceivers in communication devices.
[0084] The heat dissipator is not particularly limited, and examples thereof include heat sinks and heat spreaders that are used in combination with integrated circuit elements, transistors, optical transceiver housings, etc. Examples of materials for heat sinks and heat spreaders include copper and aluminum. In addition to heat spreaders and heat sinks, the heat dissipator may be anything that conducts heat generated from a heat source and dissipates it to the outside, and examples of the heat dissipator include radiators, coolers, die pads, printed circuit boards, cooling fans, Peltier elements, heat pipes, vapor chambers, metal covers, housings, etc. The heat pipe is, for example, a hollow structure that is cylindrical, approximately cylindrical, or flattened.
[0085] FIG. 7 is a cross-sectional view showing an example of a semiconductor device to which a thermally conductive sheet is applied. For example, as shown in FIG. 7, the thermally conductive sheet 1 is mounted on a semiconductor device 50 built into various electronic devices and sandwiched between a heat generating body and a heat dissipating body. The semiconductor device 50 shown in FIG. 7 includes an electronic component 51, a heat spreader 52, and a thermally conductive sheet 1, and the thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the electronic component 51. The thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the heat sink 53, and together with the heat spreader 52, constitutes a heat dissipation member that dissipates heat from the electronic component 51. The mounting location of the thermally conductive sheet 1 is not limited to between the heat spreader 52 and the electronic component 51, or between the heat spreader 52 and the heat sink 53, and can be appropriately selected according to the configuration of the electronic device or the semiconductor device. The heat spreader 52 is formed, for example, in a rectangular plate shape, and has a main surface 52a facing the electronic component 51 and a side wall 52b standing along the outer periphery of the main surface 52a. The heat spreader 52 has a thermally conductive sheet 1 provided on the main surface 52a surrounded by the side wall 52b, and a heat sink 53 provided, with the thermally conductive sheet 1 interposed between the main surface 52a and the other surface 52c opposite the main surface 52a. EXAMPLES
[0086] Hereinafter, examples of the present technology will be described. Note that the present technology is not limited to these examples.
[0087] <Thermal Conductive Composition A> A thermally conductive composition A was prepared by uniformly mixing 32% by volume of silicone resin, 14% by volume of aluminum oxide (average particle size: about 2 μm), 25% by volume of aluminum nitride (average particle size: about 1 μm), 28% by volume of carbon fiber (average fiber length: about 150 μm), and 1% by volume of a silane-based dispersant (n-decyltrimethoxylane). This thermally conductive composition A was poured into a mold (opening: 50 mm × 50 mm) having a rectangular parallelepiped internal space by extrusion molding, and heated in an oven at 60 ° C for 4 hours to form a columnar cured product (molded block). A polyethylene terephthalate film that had been subjected to a release treatment was attached to the inner surface of the mold so that the release-treated surface was on the inside. The obtained columnar cured product was cut (sliced) into 0.3 mm or 1.0 mm thick sheets with a slicer in a direction approximately perpendicular to the length direction of the column, to obtain a sheet-like molded product (first thermally conductive layer) in which the carbon fibers were oriented in the thickness direction. The Shore type OO hardness of the first thermally conductive layer was 70. The hardness of the first thermally conductive layer was measured using a type OO durometer on a first thermally conductive layer having a thickness of 10 mm, which was obtained by laminating 10 first thermally conductive layers having a thickness of 1.0 mm, in accordance with a method conforming to ASTM D 2240. The Shore type OO hardness of the first thermally conductive layer was the average value of the measurement results obtained by measuring 5 points on one side and 10 points on both sides in total.
[0088] <Thermal Conductive Composition B-1> Thermal conductive composition B-1 was obtained by uniformly mixing 45% by volume of silicone resin, 20% by volume of aluminum oxide (average particle size: approximately 2 μm), 30% by volume of aluminum nitride (average particle size: approximately 1 μm), and 5% by volume of a silane-based dispersant (n-decyltrimethoxysilane). The viscosity of thermal conductive composition B-1 was 20 Pa·s. The thermal conductivity of thermal conductive composition B-1, which was measured after curing at 80°C for 6 hours with a thickness of 2 mm, was 1.0 W / (m·K).
[0089] <Thermal Conductive Compositions B-1-I to B-1-V> For the thermal conductive composition B-1, the ratio of vinyl silicone at both ends with an average molecular weight of 15,000 and hydrosilyl silicone with an average molecular weight of 15,000 and an average of one Si-H at both ends and on the chain was adjusted to adjust the penetration of the silicone resin alone, to obtain thermal conductive compositions B-1-I to B-1-V. The ratio of the number of moles of hydrogen atoms directly bonded to silicon atoms to the number of moles of alkenyl groups, and the penetration of the silicone resin alone are shown in Table 1 below. The method for measuring the penetration of the silicone resin alone will be described later.
[0090] [Table 1]
[0091] <Thermal Conductive Composition B-2> Thermal conductive composition B-2 was obtained by uniformly mixing 90% by volume of silicone resin and 10% by volume of aluminum oxide (average particle size: approximately 2 μm). The viscosity of thermal conductive composition B-2 was 1 Pa·s. Thermal conductive composition B-2 was cured at 80°C for 6 hours at a thickness of 2 mm, and the thermal conductivity of thermal conductive composition B-2 was measured and found to be 0.2 W / (m·K).
[0092] <Thermal Conductive Composition B-3> Thermal conductive composition B-3 was obtained by uniformly mixing 30% by volume of silicone resin, 30% by volume of aluminum oxide (average particle size: approximately 2 μm), 35% by volume of aluminum nitride (average particle size: approximately 1 μm), and 5% by volume of a silane-based dispersant (n-decyltrimethoxysilane). The viscosity of thermal conductive composition B-3 was 150 Pa·s. The thermal conductivity of thermal conductive composition B-3, which was measured after curing at 80°C for 6 hours at a thickness of 2 mm, was 2.0 W / (m·K).
[0093] <Example 1> The thermally conductive composition B-1-I was applied to a thickness of 6 μm on a polyethylene terephthalate film of 38 μm that had been subjected to a peeling treatment. The thermally conductive composition B-1-I was transferred and coated by sandwiching both sides of a first thermally conductive layer of 0.3 mm with the film to which the thermally conductive composition B-1-I was applied. The film was then cured at 80° C. for 6 hours, and the polyethylene terephthalate film was peeled off to obtain a thermally conductive sheet in which both sides of the first thermally conductive layer were sandwiched between second thermally conductive layers made of the thermally conductive composition B-1-I.
[0094] <Example 2> In Example 2, except that the thermally conductive composition B-1-I was changed to the thermally conductive composition B-1-II, a thermally conductive sheet was obtained in the same manner as in Example 1. That is, in Example 2, a thermally conductive sheet was obtained in which both sides of a first thermally conductive layer were sandwiched between second thermally conductive layers (thickness 6 μm) made of the thermally conductive composition B-1-II.
[0095] <Example 3> In Example 3, a thermally conductive sheet was obtained in the same manner as in Example 2, except that the thickness of the second thermally conductive layer made of the thermally conductive composition B-1-II was changed to 10 μm.
[0096] <Example 4> In Example 4, except that the thermally conductive composition B-1-I was changed to the thermally conductive composition B-1-III, a thermally conductive sheet was obtained in the same manner as in Example 1. That is, in Example 4, a thermally conductive sheet was obtained in which both sides of a first thermally conductive layer were sandwiched between second thermally conductive layers (thickness 6 μm) made of the thermally conductive composition B-1-III.
[0097] <Example 5> In Example 5, except that the thermally conductive composition B-1-I was changed to the thermally conductive composition B-1-IV, a thermally conductive sheet was obtained in the same manner as in Example 1. That is, in Example 5, a thermally conductive sheet was obtained in which both sides of a first thermally conductive layer were sandwiched between second thermally conductive layers (thickness 6 μm) made of the thermally conductive composition B-1-IV.
[0098] <Reference example 1> The thermally conductive composition B-1-II was applied to a thickness of 6 μm on a polyethylene terephthalate film of 38 μm that had been subjected to a peeling treatment. The film coated with the thermally conductive composition B-1-II was pressed against one side of a first thermally conductive layer of 0.3 mm in thickness, transferring the thermally conductive composition B-1-II and coating it. The film was then cured at 80° C. for 6 hours, and the polyethylene terephthalate film was peeled off to obtain a thermally conductive sheet in which a second thermally conductive layer (6 μm thick) made of the thermally conductive composition B-1-II was provided on one side of the first thermally conductive layer.
[0099] <Comparative Example 1> In Comparative Example 1, a sheet-shaped molded product (a first thermally conductive layer having a thickness of 0.3 mm) in which carbon fibers were oriented in the thickness direction was used as is without coating. That is, in Comparative Example 1, a thermally conductive sheet was obtained in which both sides of the first thermally conductive layer were not sandwiched between second thermally conductive layers made of any of the thermally conductive compositions B-1-I to B-1-V.
[0100] <Comparative Example 2> In Comparative Example 2, except that the thermally conductive composition B-1-I was changed to the thermally conductive composition B-1-V, a thermally conductive sheet was obtained in the same manner as in Example 1. That is, in Comparative Example 2, a thermally conductive sheet was obtained in which both sides of a first thermally conductive layer were sandwiched between second thermally conductive layers (thickness 6 μm) made of the thermally conductive composition B-1-V.
[0101] <Comparative Example 3> In Comparative Example 3, except that the thickness of the thermally conductive composition B-1-IV was changed to 4 μm, a thermally conductive sheet was obtained in the same manner as in Example 5. That is, in Comparative Example 3, a thermally conductive sheet was obtained in which both sides of a first thermally conductive layer were sandwiched between second thermally conductive layers (thickness 4 μm) made of the thermally conductive composition B-1-IV.
[0102] <Comparative Example 4> In Comparative Example 4, except that the thermally conductive composition B-1-II was changed to the thermally conductive composition B-2 and the thickness of the thermally conductive composition B-2 was changed to 3 μm, a thermally conductive sheet was obtained in the same manner as in Example 2. That is, in Comparative Example 4, a thermally conductive sheet was obtained in which both sides of a first thermally conductive layer were sandwiched between second thermally conductive layers (thickness 3 μm) made of the thermally conductive composition B-2.
[0103] <Comparative Example 5> In Comparative Example 5, except that the thermally conductive composition B-1-II was changed to the thermally conductive composition B-3, a thermally conductive sheet was obtained in the same manner as in Example 2. That is, in Comparative Example 5, a thermally conductive sheet was obtained in which both sides of a first thermally conductive layer were sandwiched between second thermally conductive layers (thickness 6 μm) made of the thermally conductive composition B-3.
[0104] <Comparative Example 6> In Comparative Example 6, except that the thickness of the thermally conductive composition B-1-II was changed to 20 μm, a thermally conductive sheet was obtained in the same manner as in Example 2. That is, in Comparative Example 6, a thermally conductive sheet was obtained in which both sides of a first thermally conductive layer were sandwiched between second thermally conductive layers (thickness 20 μm) made of the thermally conductive composition B-1-II.
[0105] <Penetration> The penetration of the silicone resin alone used in the thermal conductive compositions B-1-I to B-1-V, B-2, and B-3 was measured using a penetration tester (product name EX-201, manufactured by Daiichi Rika Co., Ltd.) in accordance with JIS K 2220. Approximately 50cc of the mixed silicone resin was added to an aluminum container with a diameter of 50 mm and a height of 30 mm, and the mixture was cured at 100°C for 4 hours. The results are shown in Tables 3 and 4.
[0106] <Thermal conductivity> The cured products of the thermal conductive compositions B-1 to B-3 were punched out into a size of 20 mm in diameter using a method in accordance with ASTM-D5470, and pressed with a specified pressure (0.3 kgf / cm 2 or 0.5kgf / cm 2 The measurement was started 200 seconds after the pressure was started, and after it was confirmed that the pressure had stabilized, the average value for the next 50 seconds was taken as the measured value. The results are shown in Tables 3 and 4.
[0107] <Viscosity> The viscosities of the thermal conductive compositions B-1-I to B-1-V, B-2, and B-3 were measured using a rheometer (product name: RST-CPS, manufactured by Brookfield) with a 25 mm diameter plate (RPT-25) at a rotation speed of 10 rpm and a plate distance of 0.5 mm. The results are shown in Tables 3 and 4.
[0108] <Arithmetic mean height (Sa), skewness (Ssk), development area ratio (Sdr)> The arithmetic mean height (Sa), skewness (Ssk) and developed area ratio (Sdr) of the surface of the second thermally conductive layer were measured in accordance with ISO 25178 using a scanning white light interference microscope (product name: VS-1800, manufactured by Hitachi High-Technologies Corporation) with an objective lens set at 20x magnification for a measurement field of view of 500 μm square, after connecting four images of 500 μm square. The results are shown in Tables 3 and 4. In Table 4, the "treated surface" refers to the surface 6A of the second thermally conductive layer 6 in the thermally conductive sheet 10 shown in FIG. 6, for example, and the "non-treated surface" refers to the surface on the side where the second thermally conductive layer 6 is not formed in the thermally conductive sheet 10 shown in FIG. 6, for example.
[0109] <Thermal resistance value> Using a method in accordance with ASTM-D5470, the thermal conductive sheet is punched out to a size of 20 mm in diameter and pressed with a specified pressure (0.3 kgf / cm 2 or 0.5kgf / cm 2 The measurement was started 200 seconds after the pressure started, and after it was confirmed that the pressure had stabilized, the average value for the next 50 seconds was recorded as the measured value. The results are shown in Tables 3 and 4. For practical purposes, the thermal conductive sheet is 2 Or 0.5kgf / cm 2 The thermal resistance when the 2 / W, and preferably less than 0.30°C cm 2 It is more preferable that the ratio is 1 / W or less.
[0110] <Tackiness> The adhesiveness of the thermal conductive sheet was evaluated according to the criteria shown in Table 2 after placing a sample on an alloy (A5052P, dimensions: 0.5 mm x 50 mm x 100 mm) conforming to JIS H 4000. That is, after placing the sample on the alloy, if the sample was tilted 180° and did not fall off for 1 minute, it was evaluated as ◯ (good); if the sample fell off within 1 minute after tilting 180° and did not fall off for 1 minute after tilting 90°, it was evaluated as △ (fair); and if the sample fell off within 1 minute after tilting 90°, it was evaluated as × (poor). The results are shown in Tables 3 and 4. For practical purposes, it is preferable that the adhesiveness is evaluated as ◯ or △, and ◯ is more preferable.
[0111] [Table 2]
[0112] <Tack strength> Immediately after peeling off the release-treated PET film from the thermal conductive sheet (within 3 minutes after peeling off the PET film), a tack tester (manufactured by Malcom) was used to press the thermal conductive sheet 50μm into the sheet at 2mm / sec with a 5.1mm diameter probe and then pull it out at 10mm / sec to measure the tack force (gf) of the surface of the thermal conductive sheet. The results are shown in Tables 3 and 4.
[0113] [Table 3]
[0114] [Table 4]
[0115] From the results of Examples 1 to 5, it was found that a thermally conductive sheet comprising a first thermally conductive layer containing a first binder resin, an anisotropic thermally conductive material, and a first inorganic filler, and a second thermally conductive layer provided on both sides of the first thermally conductive layer, containing a second binder resin and a second inorganic filler, having a thickness of more than 4 μm and less than 20 μm and a thermal conductivity of 0.8 W / m·K or more, wherein the developed area ratio of the surface of the second thermally conductive layer is 35% or less and the skewness of the surface of the second thermally conductive layer is -1.0 or less as defined in ISO 25178, as measured using a scanning white light interference microscope with an objective lens of 20x, can reduce the contact thermal resistance and also reduce the thermal resistance value. The thermally conductive sheets obtained in Examples 1 to 5 had improved surface smoothness by filling the recesses of the first thermally conductive layer with the second thermally conductive layer, resulting in improved resistance to low loads (0.3 to 0.5 kgf / cm 2 It was found that the thermal conductivity in the region (above) can be improved and the thermal resistance can be reduced.
[0116] From the results of Examples 1 to 4, it was found that when the penetration of the second binder resin (addition curing silicone resin) used in the second thermally conductive layer alone was 30 to 85 as measured in accordance with JIS K 2220, not only could the contact thermal resistance of the thermally conductive sheet be reduced, but the tack of the thermally conductive sheet was also good.
[0117] From the results of Reference Example 1, it was confirmed that the thermally conductive sheet provided with the second thermally conductive layer similar to those of Examples 1 to 5 has an effect of reducing contact thermal resistance, compared to a thermally conductive sheet not provided with a second thermally conductive layer. In addition, since the thermally conductive sheet of Reference Example 1 has a difference in tack strength between both sides of the thermally conductive sheet, it is suitable for a case where, for example, during mounting, one side is left fixed to the heat generating element, and the other side includes a process of repeatedly contacting and removing a heat sink from the thermally conductive sheet to align it, and then fixing it.
[0118] From the results of Comparative Example 1, it was found that it is difficult to reduce the contact thermal resistance in a thermally conductive sheet that does not have a second thermally conductive layer on both sides of the first thermally conductive layer. Since the surface of the first thermally conductive layer of the thermally conductive sheet obtained in Comparative Example 1 is not coated with the second thermally conductive layer, the contact thermal resistance is low in the low load region (0.3 to 0.5 kgf / cm 2 It is considered that the influence of the contact thermal resistance was very large in the region (A) and the thermal resistance value was deteriorated. It was also found that the thermal conductive sheet obtained in Comparative Example 1 did not have a good tack strength.
[0119] From the results of Comparative Example 2, it was found that even in a thermally conductive sheet having a first thermally conductive layer and a second thermally conductive layer provided on both sides of the first thermally conductive layer, if the developed area ratio of the surface of the second thermally conductive layer does not satisfy the requirement of 35% or less as specified in ISO 25178, and the skewness of the surface of the second thermally conductive layer does not satisfy the requirement of -1.0 or less, as measured using a scanning white light interference microscope with an objective lens of 20x, it is difficult to reduce the contact thermal resistance.
[0120] In Comparative Example 2, since the penetration of the second binder resin (addition curing silicone resin) used in the second thermally conductive layer was more than 85, processing and handling of the second thermally conductive layer tended to be difficult, and when the polyethylene terephthalate film was peeled off, part of the thermally conductive composition B-1-V was transferred to the polyethylene terephthalate film side. Therefore, in Comparative Example 2, the development area and skewness of the surface of the second thermally conductive layer were deteriorated, and the smoothness of the surface of the thermally conductive sheet was not sufficiently improved, and it is considered that the contact thermal resistance could not be sufficiently reduced.
[0121] From the results of Comparative Example 3, it was found that even in a thermally conductive sheet having a first thermally conductive layer and a second thermally conductive layer provided on both sides of the first thermally conductive layer, the thickness of the second thermally conductive layer does not exceed 4 μm, the developed surface area ratio of the second thermally conductive layer does not satisfy 35% or less as specified in ISO 25178, and the skewness of the surface of the second thermally conductive layer does not satisfy -1.0 or less, as measured by a scanning white light interference microscope with an objective lens of 20 times, is difficult to reduce the contact thermal resistance. In Comparative Example 3, since the thickness of the second thermally conductive layer was 4 μm, the amount of the second thermally conductive layer was too small relative to the first thermally conductive layer having a thickness of 10 mm, so the smoothness of the surface of the thermally conductive sheet was not sufficiently improved, and the contact thermal resistance could not be sufficiently reduced. It was also found that the thermally conductive sheet obtained in Comparative Example 3 did not have good tack strength.
[0122] From the results of Comparative Example 4, it was found that even if the thermal conductive sheet has a first thermal conductive layer and a second thermal conductive layer provided on both sides of the first thermal conductive layer, and the developed surface area ratio of the second thermal conductive layer as specified in ISO 25178 is 35% or less and the skewness of the surface of the second thermal conductive layer is -1.0 or less, as measured by a scanning white light interference microscope with an objective lens of 20 times, it is difficult to reduce the thermal resistance value if the thermal conductivity of the second thermal conductive layer is not 0.8 W / (m·K) or more. In Comparative Example 4, since the second thermal conductive layer made of the thermal conductive composition B-2 having a relatively low thermal conductivity was used, it is considered that it was difficult to reduce the thermal resistance of the entire thermal conductive sheet, even if the bulk thermal conductivity of the second thermal conductive layer was low and the contact thermal resistance was improved, because the thermal resistance value of the second thermal conductive layer was high.
[0123] From the results of Comparative Example 5, it was found that even if the thermally conductive sheet has a first thermally conductive layer and a second thermally conductive layer provided on both sides of the first thermally conductive layer, and the developed surface area ratio of the second thermally conductive layer as specified in ISO 25178 is 35% or less as measured by a scanning white light interference microscope with an objective lens of 20 times, it is difficult to reduce the contact thermal resistance if the skewness of the surface of the second thermally conductive layer does not satisfy -1.0 or less as specified in ISO 25178. In Comparative Example 5, the second thermally conductive layer made of the thermally conductive composition B-3 having a relatively high thermal conductivity was used, but the viscosity of the second thermally conductive layer was high, and it tended to be difficult to coat the first thermally conductive layer with the second thermally conductive layer, and it is considered that the smoothness of the surface of the thermally conductive sheet was not sufficiently improved, and the contact thermal resistance could not be sufficiently reduced.
[0124] From the results of Comparative Example 6, it was found that even if the thermal conductive sheet has a first thermal conductive layer and a second thermal conductive layer provided on both sides of the first thermal conductive layer, and the surface development area ratio of the second thermal conductive layer specified in ISO 25178 is 35% or less and the surface skewness of the second thermal conductive layer is -1.0 or less, as measured by a scanning white light interference microscope with an objective lens of 20 times, it is difficult to reduce the contact thermal resistance if the thickness of the second thermal conductive layer does not satisfy the condition of less than 20 μm. In Comparative Example 6, since the thickness of the second thermal conductive layer is 20 μm, it is considered that it was difficult to reduce the thermal resistance of the entire thermal conductive sheet due to the magnitude of the thermal resistance value derived from the thickness of the second thermal conductive layer. [Explanation of symbols]
[0125] 1. Thermally conductive sheet, 2 a first thermally conductive layer; 3 a first binder resin; 4 Anisotropic thermal conductive materials, 5 a first inorganic filler; 6 a second thermally conductive layer; 6A,6B surface, 7 a second binder resin; 8 a second inorganic filler; 10 Thermally conductive sheet, 50 Semiconductor device, 51 Electronic components, 52 heat spreader, 52a main surface, 52b side wall, 52c On the other side, 53 Heat sink
Claims
1. a first thermally conductive layer containing a first binder resin, an anisotropic thermally conductive material, and a first inorganic filler; a second thermally conductive layer provided on both sides of the first thermally conductive layer, containing a second binder resin and a second inorganic filler, having a thickness of more than 4 μm and less than 20 μm, and having a thermal conductivity of 0.8 W / (m·K) or more; A thermally conductive sheet, wherein the developed area ratio of at least one of the surfaces of the second thermally conductive layer is 35% or less, and the skewness of at least one of the surfaces of the second thermally conductive layer is -1.0 or less, as defined in ISO 25178, as measured using a scanning white light interference microscope with an objective lens of 20x.
2. The thermally conductive sheet according to claim 1 , wherein the anisotropic thermally conductive material is oriented in a thickness direction in the first thermally conductive layer.
3. In the first thermally conductive layer, the content of the first binder resin is 20 to 40 volume %, and the total content of the anisotropic thermally conductive material and the first inorganic filler is 60 to 80 volume %, The thermal conductive sheet according to claim 1 or 2, wherein the content of the second binder resin in the second thermal conductive layer is 35 to 50 volume % and the content of the second inorganic filler is 50 to 65 volume %.
4. the second binder resin is an addition curing silicone resin, 3. The thermally conductive sheet according to claim 1, wherein the addition curable silicone resin alone has a penetration of 30 to 85 according to JIS K 2220.
5. 3. The thermally conductive sheet according to claim 1, which has a tack strength of 50 gf or more when a probe having a diameter of 5.1 mm is pressed 50 μm at 2 mm / sec and pulled out at 10 mm / sec.
6. 3. The thermally conductive sheet according to claim 1, wherein the developed area ratios of the surfaces of the second thermally conductive layers are both 35% or less, and the skewnesses of the surfaces of the second thermally conductive layers are both -1.0 or less.
7. forming a first thermally conductive layer containing a first binder resin, an anisotropic thermally conductive material, and a first inorganic filler; forming a second thermally conductive layer containing a second binder resin and a second inorganic filler, having a thickness of more than 4 μm and less than 20 μm, and having a thermal conductivity of 0.8 W / (m·K) or more on both sides of the first thermally conductive layer; A method for producing a thermally conductive sheet, wherein the developed area ratio of at least one of the surfaces of the second thermally conductive layer is 35% or less, and the skewness of at least one of the surfaces of the second thermally conductive layer is -1.0 or less, as defined in ISO 25178, as measured using a scanning white light interference microscope with an objective lens of 20x.
8. 8. The method for manufacturing a thermally conductive sheet according to claim 7, wherein the developed area ratios of the surfaces of the second thermally conductive layers are both 35% or less, and the skewnesses of the surfaces of the second thermally conductive layers are both -1.0 or less.
Citation Information
Patent Citations
Ultrasonic probe
JP1982052299A
Device for discriminating pattern
JP1986005388A
Manufacturing method of heat-conductive sheet
JP2020116873A
Thermal conductive sheet
JP4716102B2
Control device, information processing system and program
JP6631735B1